PENGARUH MODEL TIME TOKEN ARRENDS TERHADAP KETERAMPILAN BERBICARA SISWA KELAS V SDN 6 CAKRANEGARA - Yuliana, Heny; Intiana, Siti Rohana Hariana (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2019)
This study aims to determine the effect of the Time Token Arrends learning model on the speaking skills of fifth-grade students in Indonesian language learning at SDN 6 Cakranegara during the 2018/2019 academic year. The research used a quasi-experimental method with a pretest-posttest control group design. The sample consisted of two classes: class VA as the experimental group and class VB as the control group, each comprising 30 students. Data were collected using a performance assessment rubric to evaluate students’ speaking skills. The results showed that the calculated t-value of 12.418 was greater than the t-table value of 2.002 at a significance level of 0.05, indicating a significant effect of the Time Token Arrends model on improving students’ speaking skills. This model effectively enhances students’ active participation, learning motivation, and communication abilities during learning activities. Therefore, the Time Token Arrends model is recommended as an effective alternative speaking strategy at the elementary school level.